To evaluate the effectiveness of planned teaching programme on myth’s regarding breastfeeding on knowledge among L.S.C.S mothers of selected maternity hospitals in Sangli, Miraj, Kupwad corporation area - Mathew, Shaila; Kumbhar, Vijaya R. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The study was aimed to assess the existing knowledge regarding myths on breastfeeding, to evaluate the planned teaching programme regarding myths on breastfeeding and find out the association between pre-test knowledge score with selected demographic variables. Materials and methods: The research design used was quasiexperimental pre-test-post-test-design, and purposive sampling technique was used. The sample of the study consisted of 50 L.S.C.S. mothers who were selected as per the inclusion criteria. The tool consisted of two sections consisted of demographic data such as age, qualification, religion, type of family, and a number of gravida and previous children. The questionnaire consisted of questions related to breastfeeding and it‟s myths. Total 17 questions were included and each right answer was given a score of 1. The total score was divided into three gradings (poor, average, and good). The experts determined the content validity of the tool. The reliability of the tool was done and the result was found to be 0.70. Hence, the final tool was used for the pilot study. A pilot study was conducted on 5 subjects to check, the feasibility and practicability of the questionnaire. Results: In pre-test score, 10% mothers had poor knowledge, 86% mothers had the average knowledge, and 4% mothers had good knowledge about breastfeeding and its myths. It was evident that more efforts were necessary to improve the knowledge regarding breastfeeding and its myths among L.S.C.S mothers. In the post-test score, that 68 % mothers had the average knowledge and 32% mothers had good knowledge about breastfeeding and its myths. Mean value of pre-test knowledge score was 9.32 and post-test knowledge score was 11.58 and calculated „t‟ value was 10.228 which was more than tabulated „t‟ value and calculated „p‟ value was 0.000 which was less than tabulated „p‟ value. Conclusion: This study suggests that there is statistically significant increase in post-test knowledge score, so planned teaching programme on breastfeeding and its myths are effective.